Bacterial plasmids: the role in the development of resistance to antimicrobial compounds - Koshova, Olena; Filimonova, Nataliia; Mozghova, Larysa; Tishchenko, Iryna (ScienceRise: Biological Science, 2024)
The rapid increase in the prevalence of multiple drug resistance of pathogenic microorganisms poses a critical threat to public health worldwide, which significantly contributes to the increase in patient mortality and morbidity. Classical agents, used in the past for treatment, are losing their effectiveness, moreover, many of the newer available drugs have already become targets for bacterial resistance mechanisms. As a result, the treatment of infections becomes more complicated, and the total costs of treatment increase. Purpouse. In this work, we aimed to evaluate the role of plasmids in the development of antibiotic resistance and discuss various mechanisms of bacterial resistance to antibiotics, such as enzymatic inactivation of the antibiotic, reduction of the permeability of the outer cell membrane for the antibiotic, modification of the target mainly due to mutation, active efflux of the drug from the bacterial cell through with the help of enzymatic pumps. Materials and methods: the search for sources of information was carried out in the databases PubMed, Medline, Web of Science, Google Scholar, as well as electronic repositories of higher education institutions and scientific institutions of Ukraine. Materials related to the research technology of genetic variability and modification of bacteria and mechanisms of resistance of microorganisms to antibiotics were selected. Results. As a result of evolutionary development, bacteria have acquired two separate genetic systems - chromosomal DNA and extrachromosomal, self-replicating genetic elements called plasmids. It is bacterial plasmids that play a key role in the diffusion of specific resistance genes, in particular to antibiotics. Plasmids are non-essential parts of bacteria and are double-stranded, circular, or linear DNA molecules capable of autonomous replication, allowing bacteria to adapt to a hostile environment. Today, scientists are most interested in two properties of bacteria, caused by plasmids, - antibiotic resistance and bioremediation. The latter determines the survival and development of bacteria in various adverse conditions, including resistance to pollutants, the ability to decompose different chemical compounds, or adaptation to new ecological niches. Conclusions. Plasmids carry genes for xenobiotic degradation and heavy metal resistance, making them useful for bioremediation of toxic chemicals in an environmentally safe manner. However, properties, such as antibiotic resistance, result from the excessive and uncontrolled use of these drugs in medicine, veterinary medicine, agriculture, and other fields. Under such conditions, there is a natural selection of those strains of pathogenic bacteria that are carriers of R-plasmids